First Principle Investigations On The Electronic Structure Of Graphene Nanoribbon And Its Interaction With Muonium - Ang , Lee Sin (2010)
The results reported here are from the theoretical investigations of the graphene systems. In selecting the suitable methods for use in the simulations, a few methods, ranging from molecular orbital, post-self-consistent field, and density functional theory (in the forms of pure and hybrid functionals) are selected. B3LYP emerged as the suitable choice for use in the investigations as other methods suffer from spin contamination and the problem of efficiency. In order to find the models that are suitable for use in molecular orbitals cluster calculations, two sets of graphene nanoribbon models, one with zigzag and the other the armchair edges were investigated. It was found that the electronic properties and the geometries of the graphene nanoribbons do depend on the size of the graphene nanoribbons.